2017
DOI: 10.1186/s40885-016-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Office orthostatic blood pressure measurements and ambulatory blood pressure monitoring in the prediction of autonomic dysfunction

Abstract: BackgroundIn this retrospective analysis we investigated the predictive performance of orthostatic hypotension (OH) and ambulatory blood pressure monitoring (ABP) to predict autonomic dysfunction.MethodsStatistical associations among the candidate variables were investigated and comparisons of predictive performances were performed using Receiver Operating Characteristics (ROC) curves.ResultsNinety-four patients were included for analysis. No significant correlations could be demonstrated between OH and compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…A study by Cremer and colleagues showed that HBPM is better than OBPM in screening for orthostatic hypotension. 78 Another study showed that ABPM can predict autonomic dysfunction in orthostatic hypotension, 79 and may be useful when assessing patients for orthostatic hypoten sion. 80 Postprandial hypotension occurs when systolic BP decreases by more than 20 mm Hg within 2 h after a meal.…”
Section: Out-of-office Bp Monitoring For Screening Hypotensionmentioning
confidence: 99%
“…A study by Cremer and colleagues showed that HBPM is better than OBPM in screening for orthostatic hypotension. 78 Another study showed that ABPM can predict autonomic dysfunction in orthostatic hypotension, 79 and may be useful when assessing patients for orthostatic hypoten sion. 80 Postprandial hypotension occurs when systolic BP decreases by more than 20 mm Hg within 2 h after a meal.…”
Section: Out-of-office Bp Monitoring For Screening Hypotensionmentioning
confidence: 99%
“…ABPM is becoming recognized as a syncope diagnostic tool, with findings of both persistent and episodic hypotension (Table 2). ABPM may also reveal orthostatic, post-prandial, and post-exercise hypotension [1,[45][46][47], or hypotensive episodes following drug administration, as may be observed in Parkinsonian patients receiving dopaminergic drugs [46]. Moreover, ABPM may help to identify hypotensive susceptibility in reflex syncope.…”
Section: The Hypotensive Phenotypementioning
confidence: 99%
“…[30] Alquadan et al demonstrated that postprandial hypotension and cardiac rhythm variability computed on ABPM are potent predictors of autonomic dysfunction in routine clinical practice. [31] Frequently, patients with orthostatic hypotension may develop non-dipper hypertension profile, which is a treatment challenge for physicians. [18] Obesity Compared to normal weight, obesity is responsible for five times increase in hypertension incidence.…”
Section: Autonomic Nervous Systemmentioning
confidence: 99%